2020
DOI: 10.1177/000313482008600123
|View full text |Cite
|
Sign up to set email alerts
|

Extending Enhanced Recovery after Surgery Protocols to the Post-Discharge Setting: A Phone Call Intervention to Support Patients after Expedited Discharge after Pancreaticoduodenectomy

Abstract: The goal of this pilot study was to track patient outcomes after an expedited discharge after enhanced recovery after surgery (ERAS) pathway for pancreaticoduodenectomy (PD). A quantitative content analysis approach was used. All PD patients in a single academic medical center between February 2017 and June 2018 were called twice by specialized physician extenders after discharge. A semi-structured interview approach was used to identify patient's symptoms or concerns, proactively educate them, and provide out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The outlier outcomes of these patients is certainly multifactorial, but may be due to rare complications, the interaction of pre-existing comorbidities, and postoperative complications, or extensive operations (eg, multivisceral, vascular resection) with accompanying risk that is not well-captured using administrative coding. In addition, these outlier patients are managed differently after discharge in our practice through managed care (higher rates of discharge to a care facility or with home health, which has been associated with readmissions 46 ) and closer clinical observation (repeat visits for diagnostic procedures such as drain studies or more frequent inperson or telehealth follow-up 47 ), introducing bias in follow-up data.…”
Section: Discussionmentioning
confidence: 99%
“…The outlier outcomes of these patients is certainly multifactorial, but may be due to rare complications, the interaction of pre-existing comorbidities, and postoperative complications, or extensive operations (eg, multivisceral, vascular resection) with accompanying risk that is not well-captured using administrative coding. In addition, these outlier patients are managed differently after discharge in our practice through managed care (higher rates of discharge to a care facility or with home health, which has been associated with readmissions 46 ) and closer clinical observation (repeat visits for diagnostic procedures such as drain studies or more frequent inperson or telehealth follow-up 47 ), introducing bias in follow-up data.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with open surgery, this has led to a significantly lower occurrence of physical complications, curtailing the hospitalisation period (Begum et al, 2014; Kehlet & Wilmore, 2008). Despite the promising benefits of ERAS and improvements in patient outcomes (Ljungqvist et al, 2017; Taurchini et al, 2018), research also highlight potential challenges and unmet needs for the patients requiring additional care after discharge (Senturk et al, 2017; Takchi et al, 2020). From the patients' perspective, the article titled Regaining familiarity with own body after treatment for operable lung cancer – a qualitative longitudinal exploration illuminates how transitioning home after surgery is considered to be a critical moment requiring follow‐up for patients in ERAS (Missel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated the efficacy of clinicianinitiated, post-discharge telephone follow-up in identifying and addressing patient concerns and postoperative issues, with associated decreased emergency room visits and readmission rates. [11][12][13][14] Thus, some surgical groups have extended their ERAS protocols to include a post-discharge clinician-initiated follow-up phone call to address patient concerns or symptoms that may warrant re-evaluation by a provider. 12,15 We have previously demonstrated that approximately 33% of patients discharged after pulmonary resection experienced ongoing or new concerns after return home.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Thus, some surgical groups have extended their ERAS protocols to include a post-discharge clinician-initiated follow-up phone call to address patient concerns or symptoms that may warrant re-evaluation by a provider. 12,15 We have previously demonstrated that approximately 33% of patients discharged after pulmonary resection experienced ongoing or new concerns after return home. 15 Post-discharge clinician-initiated phone calls are an effective strategy for evaluating such concerns, enabling minor issues to be addressed via telephone counseling and providing a means to identify major issues that require escalation of the level of care.…”
Section: Introductionmentioning
confidence: 99%